Patient-derived tumor explant models of tumor immune microenvironment reveal distinct and reproducible immunotherapy responses - Rita Turpin; Karita Peltonen; Jenna H. Rannikko; Ruixian Liu; Anita N. Kumari; Daniel Nicorici; Moon Hee Lee; Minna Mutka; Panu E. Kovanen; Laura Niinikoski; Tuomo Meretoja; Johanna Mattson; et al. (OncoImmunology)
Tumor-resident immune cells play a crucial role in eliciting anti-tumor immunity and immunomodulatory drug responses, yet these functions have been difficult to study without tractable models of the tumor immune microenvironment (TIME). Patient-derived ex vivo models contain authentic resident immune cells and therefore, could provide new mechanistic insights into how the TIME responds to tumor or immune cell-directed therapies. Here, we assessed the reproducibility and robustness of immunomodulatory drug responses across two different ex vivo models of breast cancer TIME and one of renal cell carcinoma. These independently developed TIME models were treated with a panel of clinically relevant immunomodulators, revealing remarkably similar changes in gene expression and cytokine profiles among the three models in response to T cell activation and STING-agonism, while still preserving individual patient-specific response patterns. Moreover, we found two common core signatures of adaptive or innate immune responses present across all three models and both types of cancer, potentially serving as benchmarks for drug-induced immune activation in ex vivo models of the TIME. The robust reproducibility of immunomodulatory drug responses observed across diverse ex vivo models of the TIME underscores the significance of human patient-derived models in elucidating the complexities of anti-tumor immunity and therapeutic interventions.